Comparing the Mapping of Peak Ground Acceleration (PGA) Using Donovan And Campbell Methods In Java Island - Tati, Zera; Ilman, Muhammad Nafian (Proceedings of the International Conference on Green Technology, 2017)
Java, the one big Island of Indonesia is located among three major active plates namely Pacific, Indo-Australia, and Eurasia. There is subduction zone in the Southern of Java caused by collition of Indo-Australia and Eurasia. This cause high tectonic activity and so many earthquakes occurs all the time. The ground movement caused by these earthquakes has some parameters one of the most popular is Peak Ground Acceleration (PGA). The PGA value always vary every new earthquake occurs. This PGA value could be measured by accelerometer or calculated by earthquake catalog. This research was conducted to compare two models of Peak Ground Acceleration (PGA), Donovan and Campbell. These models based on  50-years of catalog earthquakes event in period 1965 – 2015 on Java with Magnitude ≥ 5 SR and the hypocenter ≤ 80 km. The Donovan method resulting in maximum land acceleration of 0.127 g at coordinates of 9 0 SL – 116 0 EL and the lowest maximum ground acceleration of 0.0213 g at coordinates of 5,50 0 SL - 105 0 EL and the Campbell method resulting in maximum land acceleration of 0.0826 g at coordinates of 9 0 SL – 116 0 EL and the lowest maximum ground acceleration of 0.0123 g at coordinates of 5,50 0 SL – 105 0 EL. The results of this research  will be compared with The Indonesian National Standard of earthquake map on 2012 which is the results obtained from both methods do not get a significant difference value and get the maximum Peak Ground Acceleration value in accordance with the history of the earthquake on the island of Java.